2010
DOI: 10.1093/ndt/gfq680
|View full text |Cite
|
Sign up to set email alerts
|

Changes in quality of life over time--Dutch haemodialysis patients and general population compared

Abstract: This study showed an improvement of HRQOL in haemodialysis patients over an 11-year period of time, independent of global changes in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 29 publications
1
42
0
Order By: Relevance
“…[1][2][3] Poorer health-related quality of life (HRQOL) is associated with increase in morbidity and mortality among patients. 4,5 Previous studies reported that HRQOL depends on treatment modality.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Poorer health-related quality of life (HRQOL) is associated with increase in morbidity and mortality among patients. 4,5 Previous studies reported that HRQOL depends on treatment modality.…”
Section: Introductionmentioning
confidence: 99%
“…Quality of life is a patient-important quality measure of care that often matters more to patients on dialysis than survival (3,9,(14)(15)(16). Researchers have found that patientreported quality of life is inversely proportional to the number of troublesome symptoms that patients report, such as pain (17,18), and treatment of symptoms improves patient quality of life (19,20).…”
Section: Problems With Current and Proposed Esrd Qip Measuresmentioning
confidence: 99%
“…A key goal for nephrology clinicians is to provide optimal patient care to maximize patient quality of life (9). However, patient perception of quality of life is multifactorial and composed of objective and subjective physical, emotional, and social aspects (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic kidney disease and renal replacement therapies (RRTs) can cause significant changes in patients' lives and can substantially reduce QoL compared with a general population. 4 QoL can be worse in these patients than in patients with cancer 5 and is worse in patients beginning HD therapy than in those receiving established long-term HD. 6 HD can provoke negative influence on QoL, because these patients have to deal with the symptoms; follow a special diet program; and reconsider their personal, social, and professional objectives.…”
Section: Introductionmentioning
confidence: 97%